Pemodelan Kasus Kematian Demam Berdarah Dengue di Provinsi Sulawesi Selatan dengan Menggunakan Model GWZIPR - Aicha, Andi Ummi Melin Aicha; Islamiyati, Anna; Jaya, Andi Kresna (ESTIMASI: Journal of Statistics and Its Application, 2026)
Dengue Hemorrhagic Fever (DHF) has spread widely throughout the region with the number of districts/cities being infected increasing to remote areas. Data on the spread or death rate from DHF in certain locations includes spatial data. The number of deaths due to DHF cases in South Sulawesi in 2019 contained 66.67% zero value, so the Geographically Weighted Zero Inflated Poisson Regression (GWZIPR) model was used to deal with spatial data that contains many zero-value observations. Based on the simultaneous test, it was found that the GWZIPR model was feasible to use with a deviation value of 100.1557. Districts/cities in South Sulawesi have various significant variables due to spatial variations between observations and areas that are closer give greater weight so that several districts/cities have the same significant variables. In the GWZIPR model with adaptive bisquare kernel weights, the variables that affect DHF mortality in all districts/cities are the percentage of drinking water facilities that meet health requirements and population density.